PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KELURAHAN DI WILAYAH KECAMATAN AMPANA KOTA KABUPATEN TOJO UNA-UNA - Palampanga, Zahid (Katalogis, 2017)
The study aims to determine and analyze simultaneous and partial influence of leadership, work environment, and discipline on the performance of urban village officers in the area of Ampana Sub-District, Tojo Una-Una District. Type of research is decsriptive causal. Method of analysis is multiple linear regressions. The study highlights that dimension with the highest mean value of leadership is ‘participation function’ of 4.47; dimension with the highest mean in work environment is ‘the relationship with colleagues’ of 4.31. While the highest mean in variable discipline is on the dimension of ‘care to the achievement of organizational goals’ of 4.45. The result of multiple linear regression test indicates that the result of f-value is 8,485 with significant value of 0.000 at 95% confidence level (α = 0,05). It proved that leadership, work environment, and discipline simultaneously have positive and significant influence on the performance of urban village officers in the area of Ampana Sub-District, Tojo Una-Una District; leadership positively and significantly influence the performance of urban village officers in the area of Ampana Sub-District, Tojo Una-Una District, while work environment and discipline have positive but insignificant influence on the performance of urban village officers in the area of Ampana Sub-District, Tojo Una-Una District. It is suggested that the office has to pay attention to the work environment so employees comfortable working. In addition, to improve the discipline of employee, rewards and punishments should apply to undisciplined employees.